2017
DOI: 10.1016/j.gerinurse.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study to examine older adults' perceptions of health: Keys to aging successfully

Abstract: Older adult health is often defined in clinical terms. Research has demonstrated that many older adults self-report aging successfully regardless of clinical health status. This qualitative study used claims data to identify older adults on three levels of health status: healthy and active, managing diseases, or very sick, to better understand how health is defined and maintained. In total, 32 participants from two cities were interviewed. Interviews were audio- and video-recorded and then transcribed. Themati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 46 publications
8
51
0
5
Order By: Relevance
“…This could be explained by the fact that aging people use less active strategies, are less focused on problem-solving or seeking assistance, and tend to resort to more passive intrapersonal coping strategies [ 32 ]. Perceptions of one's personal financial situation as well as of the family support network and coping centred on social support also have impact on QoL, as already shown [ 13 , 22 , 33 36 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This could be explained by the fact that aging people use less active strategies, are less focused on problem-solving or seeking assistance, and tend to resort to more passive intrapersonal coping strategies [ 32 ]. Perceptions of one's personal financial situation as well as of the family support network and coping centred on social support also have impact on QoL, as already shown [ 13 , 22 , 33 36 ].…”
Section: Discussionmentioning
confidence: 94%
“…Although numerous events can occur in a lifetime, including the later years, it is never too late to plan action to improve those aspects contributing to QoL [ 34 ]. Successful aging could be bolstered by suggesting programs to build skills in these areas [ 36 ]. However conflicting results have been reported and a recent study showed that aging self-perception is not easily manipulated by stereotypes priming.…”
Section: Discussionmentioning
confidence: 99%
“…The last is actively participating in society. In other words, maintaining quality of late life is the main purpose of success aging [ 8 ], and it includes multidimensional aspects, such as overall health status [ 9 ], biophysical functionalities [ 10 ], social relationships [ 11 ], and happiness [ 12 ]. Nevertheless, these dimensions are usually correlated with an elderly person’s physical fitness and daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…Physical and psychosocial functions can be maintained and improved during old age via participation in regular physical exercise. Regular physical exercise is one of the most important components for successful ageing, 12 including the preservation of both physical and cognitive function, maintenance of social interaction and continued engagement in meaningful activities.…”
mentioning
confidence: 99%